2018
DOI: 10.1016/j.ijcha.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular enlargement predicts responsiveness to tolvaptan in congestive heart failure patients with reduced ejection fraction

Abstract: BackgroundTolvaptan is a vasopressin type 2 receptor antagonist used in heart failure (HF) with refractory diuretic resistance. However, since tolvaptan is also ineffective in some HF patients with reduced ejection fraction (HFrEF), the identification of responders is important.MethodsThe study population consisted of 51 HFrEF patients who were administered tolvaptan (EF, 28 ± 7%). We defined responders as patients with a ≥50% increase in urine volume during the 24-hours after administration of tolvaptan. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…This may not only alleviate symptoms but also positively affect cardiac output and systemic organ perfusion. A pilot study by Nonin et al 23 in patients with HFrEF showed a greater response to a selective vasopressin type 2 receptor antagonist in terms of 24hour urine output in patients who had undergone adverse RV remodeling. In addition, selective vasopressin type 2 receptor antagonist responders experienced a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This may not only alleviate symptoms but also positively affect cardiac output and systemic organ perfusion. A pilot study by Nonin et al 23 in patients with HFrEF showed a greater response to a selective vasopressin type 2 receptor antagonist in terms of 24hour urine output in patients who had undergone adverse RV remodeling. In addition, selective vasopressin type 2 receptor antagonist responders experienced a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms that tolvaptan can augment diuresis and increase sodium levels in LVAD patients during the postoperative period. Vasopressin antagonists may have particular a benefit in patients with right ventricular dysfunction 10 . This is highly relevant for the LVAD population where right ventricular dysfunction is prevalent due to the chronic, advanced nature of heart failure in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with right ventricular dilation, suggesting elevated right‐sided filling pressures and right ventricular failure, have been shown to be associated with tolvaptan responsiveness. One subset of patients that may derive particular benefit from tolvaptan is those with right ventricular failure, due to the frequent association of right ventricular failure with hyponatremia, diuretic resistance, and improved clinical response to tolvaptan 7–10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studi ini juga mengidentifikasi bahwa responder tolvaptan memiliki prognosis yang lebih baik terhadap laju kematian-kardiak dan rehospitalisasi GJ dalam 120 hari. 39 Kogure et al, 2018: Sebanyak 92 pasien congestive heart failure (CHF) dianalisis secara retrospektif. Pasien dikatakan sebagai responder ketika nilai puncak keseimbangan cairan mencapai >500 mL dalam 4 hari setelah tolvaptan diberikan.…”
Section: Gagal Jantung Dan Tolvaptanunclassified